Performance, Physiological Status, and Rumen Fermentation Profiles of Pre- and Post-Weaning Goat Kids Fed Cricket Meal as a Protein Source - D. A. Astuti; A. Anggraeny; L. Khotijah; S. Suharti; A. Jayanegara (Tropical Animal Science Journal, 2019)
This study was conducted in two experiments with the objectives: (1) to evaluate nutrient intake, physiological status, and performance of pre-weaning goat kids fed with milk replacer containing cricket meal, and (2) to evaluate nutrient intake, rumen fermentation characteristics, blood profiles, and production performance of post-weaning etawah crossbred goats fed with cricket meal as a substitution of soybean meal. Twelve pre-weaning goat kids (3.78±0.50 kg BW) were divided into 3 treatments (4 replicates per treatment), i.e., kids fed with goat milk (GM), cow milk (CM), and milk replacer containing cricket meal (MR). In the second experiment, 12 post-weaning goats (12-14 kg BW) were fed with 3 dietary treatments, i.e., control ration (CM-0), ration containing 15% cricket meal (CM-15), and ration containing 30% cricket meal (CM-30). Parameters measured during 2 months observations were nutrient intake, physiological status, fermentation profiles, blood profiles, and performance. Both experiments used a completely randomized design. Results showed that there were no significant differences in physiological status parameters in pre-weaning goat kids fed with GM, CM or MR. The performance of kids fed with GM was significantly higher (120 g/d) than those fed with CM and MR treatments (p<0.05). In the second experiment, results showed that fat intake in CM-30 was higher than the other treatments (p<0.05), meanwhile dry matter and nutrient intakes were similar. The average daily gain (ADG), feed efficiency, and rumen fermentation profiles were similar in all treatments. It is concluded that cricket meal can be used in milk replacer without any negative effect on health status. CM-30 ration has good palatability without any negative effect on the rumen fermentation profiles.